BOOK REVIEW : The Appearances of Memory. Mnemonic Practices of Architecture and Urban Form in Indonesia - Alexander R. Cuthbert (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2014)
-